Development of Halal Tourism Villages Based on Local Culture and Sustainability - Sri Harini; Rita Rahmawati; Endang Silaningsih; Immas Nurhayati; Isbandriyati Mutmainah; Bambang Hengky Rainanto; Endri Endri (Tourism and Hospitality, 2025)
The objectives of this study are, firstly, to determine the impact of tourism village development on economic, social, cultural, and environmental aspects in supporting the achievement of Sustainable Development Goals (SDGs) and, secondly, to formulate a halal, local culture-based, and sustainable tourism village development model. The research method was qualitative and quantitative. Survey data were collected using questionnaires and interviews. The data were analyzed using a difference test before and after the development of the tourism village. Based on the data analysis, significant differences in economic, social, cultural, and environmental aspects existed before and after the development of the Benteng Ciampea tourism village in Bogor Regency, Indonesia. Many studies have examined the impact of tourism village development on social, economic, cultural, and environmental aspects. However, no comprehensive research has been conducted that is supported by empirical data. Most studies have been conducted partially and not linked to the SDGs. The SDGs issue distinguishes this from previous studies on developing sustainable halal tourism villages.